Antifungal Polymeric Materials and Nanocomposites - Ntow-Boahene, Winnie; Cook, David; Good, Liam (Frontiers in Bioengineering and Biotechnology, 2021)
Rising global populations due to medicinal advancements increases the patient population susceptible to superficial and severe fungal infections. Fungi often implicated in these diseases includes the dermatophytes (Microsporum spp., Epidermophtyon spp., Trichophyton spp.) as well as species of the Candida spp., Aspergillosis spp. and Cryptococcus spp. genera. Current antifungal strategies are based mainly on small molecule antifungal drugs. However, these drugs are limited by poor drug solubility and reduced bioavailability whilst systemic administration is associated with hepatoxicity and nephrotoxicity. In addition, antimicrobial resistance against these drugs are on the rise. Thus, antimicrobial polymers offer an alternative antifungal strategy. Antifungal polymers are characterised by cationic and hydrophobic regions where the cationic regions have been shown to interact with microbial phospholipids and membranes. These polymers can be synthetic or natural and demonstrate distinct antifungal mechanisms ranging from fungal cell membrane permeabilisation, cell membrane depolarisation or cell entry. Although the relative importance of such mechanisms is difficult to decipher. Due to the chemical properties of these polymers, they can be combined with other antimicrobial compounds including existing antifungal drugs, charcoals, lipids and metal ions to elicit synergistic effects. In some cases, antifungal polymers and nanocomposites show better antifungal effects or reduced toxicity compared to the widely used small molecule antifungal drugs. This review provides an overview of antimicrobial polymers and nanocomposites with antifungal activity and the current understanding of their antifungal mechanisms.